The role of prokaryotic mercury methylators and demethylators in Canadian Arctic thermokarst lakes - Nicola Gambardella; Joana Costa; Beatriz Malcata Martins; Diogo Folhas; Ana Patrícia Ribeiro; Holger Hintelmann; João Canário; Catarina Magalhães (Scientific Reports)
Abstract Permafrost soils are critical reservoirs for mercury (Hg), with the thawing process leading to the release of this element into the environment, posing significant environmental risks. Of particular concern is the methylated form of mercury, monomethylmercury (MMHg), known for its adverse effects on Human health. Microbial communities play a pivotal role in the formation of MMHg by facilitating Hg methylation and in the demethylation of MMHg, slowing the crossing of toxic threshold concentration in the environment. However, the specific microbes involved still need to be understood. This study aimed to identify the microbial drivers behind changes in Hg speciation (MMHg and Hg) in permafrost thaw lakes and assess the significance of the biotic component in Hg biogeochemistry. Sediment samples from two thermokarst lakes in the Canadian sub-Arctic were collected during the winter and summer of 2022. Gene-centric metagenomics using whole-genome sequencing (WGS) was employed to identify key genes involved in mercury methylation (hgcA and hgcB) and demethylation (merA and merB), supported by qPCR analyses. A seasonal decline in microbial diversity, involved in the Hg methylation, and hgcA gene coverage was observed from winter to summer, mirroring patterns in mercury methylation rates. Notably, hgcA sequences were significantly more abundant than merAB sequences, with contrasting seasonal trends. These results indicate a seasonal shift in the microbial community, transitioning from a dominance of mercury methylation in winter to a predominance of mercury demethylation in summer. Environmental drivers of these dynamics were integrated into a conceptual model. This study provide new insights on the microbial processes influencing the Hg cycle in Arctic permafrost undergoing degradation.